Multikinase inhibitors modulate non-constitutive proteasome expression in colorectal cancer cells - Burov, Alexander; Grigorieva, Ekaterina; Lebedev, Timofey; Vedernikova, Valeria; Popenko, Vladimir; Astakhova, Tatiana; Leonova, Olga; Spirin, Pavel; Prassolov, Vladimir; Karpov, Vadim; Morozov, Alexey (Frontiers in Molecular Biosciences, 2024)
Introduction: Proteasomes are multi-subunit protein complexes responsible for protein degradation in cells. Immunoproteasomes and intermediate proteasomes (together non-constitutive proteasomes) are specific forms of proteasomes frequently associated with immune response, antigen presentation, inflammation and stress. Expression of non-constitutive proteasome subunits has a prognostic value in several types of cancer. Thus, factors that modulate non-constitutive proteasome expression in tumors are of particular interest. Multikinase inhibitors (MKIs) demonstrate promising results in treatment of cancer. At the same time, their immunomodulatory properties and effects on non-constitutive proteasome expression in colorectal cancer cells are poorly investigated. Methods: Proteasome subunit expression in colorectal cancer was evaluated by bioinformatic analysis of available datasets. Two colorectal cancer cell lines, expressing fluorescent non-constitutive proteasomes were treated with multikinase inhibitors: regorafenib and sorafenib. The proteasome subunit expression was assessed by real-time PCR, Western blotting and flow cytometry. The proteasome activity was studied using proteasome activity-based probe and fluorescent substrates. Intracellular proteasome localization was revealed by confocal microscopy. Reactive oxygen species levels following treatment were determined in cells. Combined effect of proteasome inhibition and treatment with MKIs on viability of cells was estimated. Results: Expression of non-constitutive proteasomes is increased in BRAF-mutant colorectal tumors. Regorafenib and sorafenib stimulated the activity and synthesis of non-constitutive proteasomes in examined cell lines. MKIs induced oxidative stress and redistribution of proteasomes within cells. Sorafenib stimulated formation of cytoplasmic aggregates, containing proteolyticaly active non-constitutive proteasomes, while regorafenib had no such effect. MKIs caused no synergistic action when were combined with the proteasome inhibitor. Discussion: Obtained results indicate that MKIs might affect the crosstalk between cancer cells and immune cells via modulation of intracellular proteasome pool. Observed phenomenon should be considered when MKI-based therapy is applied.